2014
DOI: 10.1007/s12011-014-0136-z
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Thermocycling on Nickel Release from Orthodontic Arch Wires: an In Vitro Study

Abstract: The amount of daily intake of metals from orthodontic appliances over time is a matter of great concern. Nickel results in one of the most common metal-induced allergic contact dermatitis in humans; it produces more allergic reactions than all the other metals combined together. The purpose of this study was to evaluate the effects of thermocycling on the nickel release from orthodontic arch wires stored in artificial saliva with different pH values. Forty new wire pieces were selected. Each wire piece was pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As mentioned earlier in the introduction section, smooth surface wires are used in clinical trials. However, useful changes in form should be ( 1 - 35 ) made to provide tooth movement ( 28 ). This is the limitation the present study did not attempt to evaluate clinically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier in the introduction section, smooth surface wires are used in clinical trials. However, useful changes in form should be ( 1 - 35 ) made to provide tooth movement ( 28 ). This is the limitation the present study did not attempt to evaluate clinically.…”
Section: Discussionmentioning
confidence: 99%
“…In orthodontics, tooth movements are achieved by the forces developed in the deformed wire, which are transmitted to the teeth through fixed or removable appliances. The appliance is continuously subjected to masticatory forces, and hence the wire must be sufficiently resilient to resist permanent deformation and thermocycling and maintain its activation ( 1 , 2 ). One of the challenges of fixed orthodontic appliances is uneven arch-wire surfaces that cause friction between the wire and bracket in sliding mechanisms ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies reported in the literature demonstrate the importance of released metal ions' identification from alloys in the evaluation of toxic effects. 2,16,29,30,[32][33][34] In the study reported by Marigo et al, 13 the samples analyzed in the anatomical absorption spectrophotometer showed extremely low amounts of Ti, Al, and V in all groups tested. However, significantly higher concentrations of magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, manganese, iron, cobalt, copper, zinc, nickel, and chromium were observed when wires, brackets, and metal bands were stored in artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
“…The harmful effects of nickel have been systematically investigated at the levels of the cells, tissues, organs, and organisms. 2,3 According to the International Agency for Research on Cancer, nickel compounds are classified as carcinogenic to humans, but it is still unclear which forms of nickel pose the greatest risk. 4,5 Nickel complexes in the form of arsenides and sulphides are carcinogenic, allergenic, and mutating substances even at nontoxic concentrations.…”
mentioning
confidence: 99%